Implementation of MVC (Model View Controller) Method Development of Web-Based Administrative Applications in the Office of Muara Sungai Village Prabumulih City - Fadila Rizki; Khana wijaya; Rishi Suprianto (Yayasan Kita Menulis, 2024)
The village administration system is a website-based application that is important for village, including admins is carrying out village administration sevices which have a very important role in the government managing. All communities need to reiceve good village administration services. Data from this researcher was obtained based on interviews, direct observation at the muara sungai village office. The development method used is rad (rapid application development) which consists of requiretmens planning, design implementation processes. The language used is PhpMySql, a database operation that allows data selection or data entry, which can be done easily and automatically.